Gender Education Gaps among Indigenous and Nonindigenous Groups in Bolivia - Reimão, Maira Emy; Taş, Emcet O. (World Bank, Washington, DC, 2015)
This paper studies gender education gaps among indigenous and nonindigenous groups in Bolivia. Using the National Census of Population and Housing 2012 and an estimation method analogous to difference-in-differences, the paper finds that the intersection of gender and indigenous identity confers cumulative disadvantage for indigenous women in literacy, years of schooling, and primary and secondary school completion. Although gender education gaps have become narrower across generations, there remain significant differences among indigenous groups. The Aymara have the largest gender gap in all outcomes, despite having high overall attainment rates and mostly residing in urban centers, with greater physical access to schools. The Quechua have relatively smaller gender gaps, but these are accompanied by lower attainment levels. The paper discusses the possible sources of these differentials and highlights the importance of taking gender dynamics within each indigenous group into greater consideration.